KEBIJAKAN DIVIDEN DI SEKTOR PERBANKAN INDONESIA: ANALISIS PERAN KEBIJAKAN UTANG - Meiwarati, Eka; Hamzah, Ruth Samantha (Gapenas Publisher, 2025)
The study identifies the factors that impact the extent of dividend distributions in Indonesian banking companies during the period from 2016 to 2019. The sample comprises 30 companies. The analysis technique used moderated regression analysis. The results indicate that Return on Equity (ROE) has a significant influence on dividend policy. However, the size of the company does not exert any influence on dividend policy. Additionally, debt policy plays a moderating role in affecting the relationship between ROE and dividend policy. On the other hand, debt policy does not moderate the impact of company size on dividend policy. The implications of this study value for banking companies in Indonesia as they consider and formulate dividend policies. These findings provide insights into the factors that should be taken into account when determining dividend policies, with a focus on the key factors that influence such decisions.